1998
DOI: 10.1074/jbc.273.34.21933
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of a Variety of Polymerases to Synthesize Past Site-specific cis-syn, trans-syn-II, (6–4), and Dewar Photoproducts of Thymidylyl-(3′→5′)-thymidine

Abstract: The role of photoproduct structure, 3 3 5 exonuclease activity, and processivity on polynucleotide synthesis past photoproducts of thymidylyl-(3 3 5)-thymidine was investigated. Both Moloney murine leukemia virus reverse transcriptase and 3 3 5 exonuclease-deficient (exo ؊ ) Vent polymerase were blocked by all photoproducts, whereas Taq polymerase could slowly bypass the cis-syn dimer. T7 RNA polymerase was able to bypass all the photoproducts in the order cis-syn > Dewar > (6 -4) > trans-syn-II. Klenow fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 95 publications
4
46
1
Order By: Relevance
“…This holds true for damage-containing templates as shown with the T7 pol and the E. coli pol I, pol II, and pol III enzymes (67)(68)(69)(70). Thus, if DnaE has a proofreader, it is likely that the DnaE-proofreader complex exhibits a lower bypass capacity than described here for the purified DnaE protein.…”
Section: Dual Function Of Polymerase Dnaementioning
confidence: 79%
“…This holds true for damage-containing templates as shown with the T7 pol and the E. coli pol I, pol II, and pol III enzymes (67)(68)(69)(70). Thus, if DnaE has a proofreader, it is likely that the DnaE-proofreader complex exhibits a lower bypass capacity than described here for the purified DnaE protein.…”
Section: Dual Function Of Polymerase Dnaementioning
confidence: 79%
“…Biochemical and structural studies with the T7 Pol have shown that this Pol inserts an A opposite the 3Ј T of a CPD with the photoproduct lying outside the active site, whereas insertion opposite the 5Ј T occurs with the CPD in the active site (31,32,34). Thus, the A incorporation opposite the 3Ј T of a CPD is not template-directed but rather occurs via an abasic site-like intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…The log reduction of MS2 was calculated as log reduction ϭ log͑C 0͒ Ϫ log͑C͒ (4) where log(C 0 ) is the log concentration of the unexposed sample obtained from the regression analysis and log(C) is the measured log concentration.…”
Section: Methodsmentioning
confidence: 99%
“…UV light induces damage to the genomes of bacteria, protozoa, and viruses, breaking bonds and forming photodimeric lesions in nucleic acids, DNA, and RNA (1,2). These lesions prevent both transcription and replication and ultimately lead to inactivation of the microorganisms (3,4). Direct UV damage to nucleic acids occurs at the wavelengths absorbed by DNA and RNA, in the germicidal UV region between 200 and 300 nm (5,6).…”
mentioning
confidence: 99%